LAMINITIS IN DONKEY – A CASE REPORT - G. Kalaiselvi; N. Daniel Joy Chandran; M.Vidhya (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Laminitis is inflammation of sensitive laminae of the foot in horses and donkey. The front hooves are most commonly affected than hind feet. Laminitis can be mechanical or systematic, acute or chronic, unilateral or bilateral or sometimes all four feet were affectedDonkeys appear to be particularly susceptible to laminitis may be due to live in the desert and dry area so their ‘good bacteria’ are even more sensitive to carbohydrate overload than those of ponies and horses there certainly is no lush grass in the desert and dry area. A two year old male donkey walking very tenderly and repeated raising of left hind leg. The affected hind leg foot was cleaned with 1% Kmno4 solution for avoiding secondary bacterial infection Inj. Meloxicam 35mg I/M, in, inj. Strepto penicillin 500mg I/M were given. The affected left hind leg was exposed to infra red light for 5 minutes and hot fomentation was given with hot salt and hot rice bran mixture. Iodine ointment was applied over the swollen coronary band area of left foot.